Return Saham di Tinjau dari Profitabilitas - Rosyada Rosyada (I-Finance Journal, 2022)
ABSTRAK This study aims to determine the impact of profitability on stock returns in companies listed on the Jakarta Islamic Index 70 proxied by stock returns. The total population of companies listed on the JII during the study period was 70 companies. The sempel retrieval technique in this research is purposive sampling and 17 companies are obtained as sempel for this study. The analysis technique used to analyze the data is multiple linear regression with a significant level of 5% and hypothesis testing using the t test and F test. The results of this study indicate that the ROA variable affects stock returns with a t value of 2.853> t table 2.01410 and a significance value of 0.007 <0.05. The EPS variable has no effect on stock returns with a t value of 0.047 < t table 2.01410 with a significance value of 0.963 > 0.05. Then simultaneously the ROA and EPS variables affect stock returns with a calculated F value of 4.286> Ftable 3.21 and a significance of 0.020 <0.05. The conclusion shows that simultaneously the ROA and EPS variables have an influence on stock returns, while partially only the ROA variable has an influence on stock returns.